Conceptual Design Approach of Hybrid UAV (Huav): Technology Enabler for Aerotourism in Malaysia - Mustapha, Faizal; Ismail, Fathilah; Puad Mat Som, Ahmad; Azmin, Fairul; Na’im Abdullah, Mohd; Alia Fahada W Ab Rahman, N; ., . (International Journal of Engineering and Technology, 2018)
The introduction of Aerotourism using Unmanned Aerial Vehicle (UAV) is timely due to the importance of strong, positive destination image and how it works to influence tourist destination selection and satisfaction, as well as destination sustainability. UAV has certain advantages over piloted aircraft missions, which include the lower operating cost, improved safety, flexibility in mission planning, less expensive remote sensing platform, more rapid deployment capability than piloted aircraft and closer proximity to the target requirement.Â The increasing trend of UAV (fixed wing and rotorcraft) as part of image capturing and live telecasting has prompted many tourism operators to migrate into this autonomous technology. Unfortunately, due to its restricted design configurations and requirements related to fixed wing and rotorcraft UAV such as the need for landing strip and long endurance has receded the ultimatum usage of this technology. This paper aims to develop a conceptual framework of Aerotourism for destination image enhancement, as well as addresses the conceptual approach of Hybrid UAV (hUAV) by integrating fixed wing with rotorcraft. It is predicted that this enabling technology will achieve the smooth transition from hover to cruising and the realization of Aerotourism in Malaysia. This research could be considered as a breakthrough for Malaysian destination image, thus it could further boost the tourism industry in Malaysia.Â Â